Eukaryotic DNA polymerases. (December 2018) - Jain, Rinku; Aggarwal, Aneel K; Rechkoblit, Olga
Highlights: Humans encode 16 bone-fide DNA polymerases. Replicative DNA polymerases are emerging as highly flexible and dynamic in their interactions. Mutations in replicative polymerases (Polδ and Polε) underlie many hypermutated cancers. PrimPol is the newest entrant to the TLS superfamily. TLS polymerases are promising targets in cancer therapy. Abstract : The eukaryotic DNA replication machinery is conserved from yeast to humans and requires the actions of multiple DNA polymerases. In addition to replicative DNA polymerases for duplication of the leading and lagging DNA strands, another group of specialized polymerases is required for DNA repair and/or translesion DNA synthesis (TLS). We emphasize here recent findings that accelerate our understanding of the structure and mechanisms of these remarkable enzymes. We also highlight growing evidence on the role of DNA polymerases in the origin of certain cancers, and paradoxically as emerging targets for cancer therapy.